Chitin and chitosan as natural flocculants for beer clarification. (December 2015) - Gassara, Fatma; Antzak, Candice; Ajila, Chandran Matheyambath; Sarma, Saurabh Jyoti; Brar, Satinder Kaur; Verma, M.
Highlights: Chitin and chitosan are better than traditional coagulants for beer clarification. Higher turbidity reduction with 160 times lower dosage than traditional clarifier. Chitosan reduces the zeta potential, viscosity and phenolic content of beer. Feasibility of pilot scale application was studied using a 1000 L reactor. Abstract: Flocculation plays a central role in the way beer is produced. The primary function of flocculation is particle removal that can impart color to beer, create turbidity, and/or retain bacterial organisms. This study was carried out to investigate if carbon chitin and chitosan can be used as heterogeneous flocculants in the treatment of beer. A series of experiments were conducted in which the efficiency of chitin and chitosan was compared with the efficiency of traditional stabifix and bentonite used by the industry in the flocculation process. Turbidity, viscosity, total solids, total suspended solids, total polyphenols and the zeta potential were used to monitor the progress of the flocculation process. Both chitin and chitosan demonstrated the ability to flocculate colloidal particles in the beer. Of all the tested flocculants, chitosan (5 mg/L) was found to be the most effective.